Techniques of Illusion A Cultural and Media History of Stage Magic in the Late Nineteenth Century - Rein, Katharina (Taylor & Francis, 2023)
This book explores stage conjuring during its "Golden Age", from 1860 to 1910. This study provides close readings highlighting four paradigmatic illusions of the time that stand in for different kinds of illusions typical of stage magic in the "Golden Age" and analyses them within their cultural and media-historical context: "Pepper's Ghost", the archetypical mirror illusion; "The Vanishing Lady", staging a teleportation in a time of a dizzying acceleration of transport; "the levitation", simulating weightlessness with the help of an extended steel machinery; and "The Second Sigh", a mind-reading illusion using up-to-date communication technologies. These close readings are completed by writings focusing on visual media and expanding the scope backwards and forwards in time, roughly to 1800 and to 2000. This exploration will be of great interest to students and scholars in theatre and performance studies.